IMPROVING ELEMENTARY SCHOOL TEACHERS’ SKILLS IN USING THINK TALK WRITE LEARNING MODEL THROUGH ACADEMIC SUPERVISION - Asnawati Asnawati; Ary Kiswanto Kenedi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This research was motivated by the fact that most of the learning processes were not in accordance with the characteristics of elementary school students so that it had an impact on the quality of learning at schools that did not achieve the goal. The learning process included the process of planning, implementing, and assessing of the primary school teacher. The purpose of this study was to improve the teachers’ skills in carrying out the learning process by using a cooperative model of Think Talk Write type. This research was a school action research that adapted Mc Taggart and Kemmist's classroom action research design. This research consisted of stages of planning, implementation, observation and reflection. This research activity was carried out at SDN 23 Ujung Gurun Padang involving 10 teachers. The data collection technique was an observation sheet measuring the results of the learning process which including planning skills, implementation abilities, and assessment abilities. The data analysis technique consisted of quantitative data. The research found that the teacher's average score in carrying out the learning process using the Think Talk Write type cooperative model in cycle 1 was 68.30 and got an average score of 85.46 in cycle 2. This proved that there was an increase in teachers’ skills in carrying out the learning process by using a Think Talk Write type cooperative model through academic supervision activities. The implications of this research was that this model could be used as a reference for academic supervisors to improve the quality of learning for elementary school teachers.